Konsep transformasi digital dalam pendidikan tinggi berbasis teknologi informasi - Ba’Alawy, Quthbuddin Muhammad (Maliki Interdisciplinary Journal, 2026)
Digital transformation in higher education has become a critical topic, as the rapid growth of information technology effects learning systems and academic management. The purpose of this study is to investigate the idea of digital transformation in IT-based higher education and pinpoint the variables that affect its effectiveness. Using a variety of sources from the UIN Maulana Malik Ibrahim Malang repository and pertinent scientific journals, a qualitative literature analysis was employed as the research methodology. The results of the study reveal that digital transformation covers not only the use of technology in the learning process, such as the Learning Management System (LMS), but also the digitization of academic services, policy formulation, and changes in organizational culture. The successful implementation of digital transformation is influenced by the preparedness of technology infrastructure, human resource competencies, and institutional support. Furthermore, digital transformation also plays a role in improving learning effectiveness, service efficiency, and the overall quality of higher education. However, there are still a number of obstacles to its implementation, including low digital literacy and restricted access to technology. For the best possible digital transformation, a well-thought-out and long-term plan is therefore required.